Bio‐Nanocomposite Coatings: Multifunctional Bio‐Nanocomposite Coatings for Perishable Fruits (Adv. Mater. 26/2020). Issue 26 (1st July 2020) - Jung, Seohui; Cui, Yufei; Barnes, Morgan; Satam, Chinmay; Zhang, Shenxiang; Chowdhury, Reaz A.; Adumbumkulath, Aparna; Sahin, Onur; Miller, Corwin; Sajadi, Seyed M.; Sassi, Lucas M.; Ji, Yue; et al.
Abstract : In article 1908291, Muhammad M. Rahman, Pulickel M. Ajayan, and co‐workers present a conformal bio‐nanocomposite coating based on cellulose nanocrystals and poly(albumen) that increases the shelf‐life of fresh produce by retarding ripening, dehydration, and microbial attack. The coating is edible, easily washable, and made from readily available inexpensive materials, which makes it a promising solution to combat food wastage.